1989
DOI: 10.1055/s-0038-1646877
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activators and Plasminogen Activator Inhibitors in Liver Deficiencies Caused by Chronic Alcoholism or Infectious Hepatitis

Abstract: SummaryPlasma concentrations of tissue-type plasminogen activator (t-PA), urokinase (u-PA), plasminogen activator inhibitor 1 (PAI-1) and PAI-2 were studied in 53 patients with liver deficiency caused by chronic alcoholism (n = 40), viral hepatitis (n = 10) or malignant disease of the liver (n = 3) and compared to that of a control group (n = 20) of healthy subjects. u-PA and PAI-1 levels were significantly increased in all patients with chronic alcoholism, whereas high t-PA was only observed in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 7 publications
3
28
1
1
Order By: Relevance
“…Our results lend further support to numerous previous reports showing that fibrinolysis is up-regulated in cirrhotic patients [1][2][3][4][5][6] and provide for the first time evidence suggesting that a defect in the TAFI pathway, because of a deficiency of circulating TAFI and probably, at least in the more severe cases, because of impaired thrombin generation, may contribute to hyperfibrinolysis and possibly to bleeding associated with cirrhosis. Hyperfibrinolysis, either assessed by global fibrinolytic assays or by plasma levels of fibrin(ogen) degradation products plus t-PA antigen or activity, has been reported to be a predictor of bleeding in cirrhotic patients, [33][34][35] and there is evidence that antifibrinolytic drugs may be effective for the treatment of bleeding complications.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results lend further support to numerous previous reports showing that fibrinolysis is up-regulated in cirrhotic patients [1][2][3][4][5][6] and provide for the first time evidence suggesting that a defect in the TAFI pathway, because of a deficiency of circulating TAFI and probably, at least in the more severe cases, because of impaired thrombin generation, may contribute to hyperfibrinolysis and possibly to bleeding associated with cirrhosis. Hyperfibrinolysis, either assessed by global fibrinolytic assays or by plasma levels of fibrin(ogen) degradation products plus t-PA antigen or activity, has been reported to be a predictor of bleeding in cirrhotic patients, [33][34][35] and there is evidence that antifibrinolytic drugs may be effective for the treatment of bleeding complications.…”
Section: Discussionsupporting
confidence: 79%
“…1 Of particular relevance to hyperfibrinolysis are the imbalance between tissue plasminogen activator (t-PA) and its specific inhibitor (PAI-1), which results in an enhancement of free t-PA in the circulation and the reduction of ␣ 2 -plasmin inhibitor (␣ 2 -PI). [2][3][4][5][6] In recent years, a new plasma protein has been identified that may play an important regulatory role in fibrinolysis. It is a procarboxypeptidase synthesized by the liver and named thrombin activatable fibrinolysis inhibitor (TAFI) or procarboxypeptidase B or U.…”
mentioning
confidence: 99%
“…Indeed, PAI-1 levels during disease development are a predictor of later severity [79]. A recent human study further supports the hypothesis that PAI-1 plays a critical role in ALD [80].…”
Section: Fibrin/clottingmentioning
confidence: 50%
“…There is general agreement that pa tients with liver cirrhosis had increased val ues of t-PA antigen [71][72][73][74] probably depen dent on reduced hepatic clearance [75,76] while the measure of PAI gave conflicting results. Tran-Thanget al [77] found high val ues of PAI in LC but they did not distinguish between the patients according to the severity of liver failure. Boks et al [72] found a con siderable variability of fast-acting PA inhibi tor, which was higher in cirrhotic patients than in normal subjects; however, in patients with more severe liver insufficiency very low values of PAI were observed.…”
Section: Hyperfibrinolytic Syndromementioning
confidence: 99%